1998
DOI: 10.1002/(sici)1097-0223(199812)18:12<1294::aid-pd433>3.3.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal ultrasonographic diagnosis of the cerebro–costo–mandibular syndrome: case report and review of the literature

Abstract: We present an antenatal ultrasonographic diagnosis of the cerebro-costo-mandibular syndrome. This rare dysmorphic disorder (only 51 cases have been reported to date) mainly associates defective costal development with features of the Pierre-Robin syndrome. The diagnosis is very often made at birth and the prognosis is very poor. Antenatal ultrasound examination may show a combination of orofacial and chest maldevelopment. In our case the diagnosis was made at 20 weeks' gestation during a routine ultrasound exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Patients with CCMS have a narrow chest and striking posterior rib gaps which distinguish this condition. CCMS was first described 50 years ago [Smith et al, ] and over 80 cases have been reported to date [Kringelbach and Hendriksen, ; Doyle and McNicholl, ; McNicholl et al, ; Miller et al, ; Williams and Sane, ; Harris and Fellows, ; Silverman et al, ; Leroy et al, ; Hennekam et al, ; Merlob et al, ; Drossou‐Agakidou et al, ; Plotz et al, ; Ibba et al, ; Megier et al, ; van den Ende et al, ; Kirk et al, ; Beluffi et al, ; Flodmark and Wattsgård, ; Morin et al, ; James and Aftimos, ; Wilcox and Tatum, ; Frulio et al, ; Oestreich and Stanek, ; So et al, ; Su et al, ; Lynch et al, ; Watson et al, ; Bacrot et al, ; Ramaswamy et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with CCMS have a narrow chest and striking posterior rib gaps which distinguish this condition. CCMS was first described 50 years ago [Smith et al, ] and over 80 cases have been reported to date [Kringelbach and Hendriksen, ; Doyle and McNicholl, ; McNicholl et al, ; Miller et al, ; Williams and Sane, ; Harris and Fellows, ; Silverman et al, ; Leroy et al, ; Hennekam et al, ; Merlob et al, ; Drossou‐Agakidou et al, ; Plotz et al, ; Ibba et al, ; Megier et al, ; van den Ende et al, ; Kirk et al, ; Beluffi et al, ; Flodmark and Wattsgård, ; Morin et al, ; James and Aftimos, ; Wilcox and Tatum, ; Frulio et al, ; Oestreich and Stanek, ; So et al, ; Su et al, ; Lynch et al, ; Watson et al, ; Bacrot et al, ; Ramaswamy et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…The only method using in prenatal diagnosis is ultrasonographic examination. Megier et al reported a case with CCMS diagnosed prenatally for the first time 8 . Polyhydramnios and a very unusual shape of the ribs were documented as ultrasonographic findings of CCMS 8,9 …”
Section: Discussionmentioning
confidence: 99%
“…Cerebrocostomandibular syndrome was diagnosed on the basis of micrognathia, a posterior cleft palate defect, and characteristic rib gap abnormalities (not shown) in the neonate. 6,7 A B Figure 2. Pierre Robin sequence (case 1), 18.9 menstrual weeks.…”
Section: Discussionmentioning
confidence: 99%